Isolation and recovery of microbial polyhydroxyalkanoates (eXPRESS Polymer Letters)
The deleterious environmental impacts caused by plastic wastes have attracted worldwide concern. The biobased and biodegradable polyhydroxyalkanoate (PHA) appears to be one of the potential candidates to replace some conventional plastics. However, high production cost of PHAs has limited their market penetration. The major cost absorbing factors are the upstream fermentation processes and the downstream PHA recovery technologies. The latter significantly affects the overall process economics. Various recovery technologies have been proposed and studied in small scales in the laboratory as well as in industrial scales. These include solvent extraction, chemical digestion, enzymatic treatment and mechanical disruption, supercritical fluid disruption, flotation techniques, use of gamma irradiation and aqueous two-phase system. This paper reviews all the recovery methods known to date and compares their efficiency and the quality of the resulting PHA. Some of the large-scale production of PHA and the strategies employed to reduce the production cost are also discussed.